Neutrophils in Post-myocardial Infarction Inflammation: Damage vs. Resolution? - Puhl, Sarah-Lena; Steffens, Sabine (Frontiers in Cardiovascular Medicine, 2019)
Inflammation not only plays a crucial role in acute ischemic cardiac injury, but also contributes to post-infarction repair and remodeling. Traditionally, neutrophils have been merely considered as detrimental in the setting of an acute myocardial infarction. However, recently published studies demonstrated that neutrophils might also play an important role in cardiac repair by regulating reparative processes. An emerging concept is that different neutrophil subsets exist, which might exhibit separate functional properties. In support of the existence of distinct neutrophil subsets in the ischemic heart, transcriptional changes in cardiac neutrophils have been reported within the first few days after myocardial infarction. In addition, there is an increasing awareness of gender-specific differences in many physiological and pathophysiological responses, including cardiovascular parameters and inflammation. Of particular interest in this context are recent experimental data dissecting sex-specific differences in neutrophil signaling after myocardial infarction. Unraveling the distinct and possibly stage-dependent properties of neutrophils in cardiac repair may provide new therapeutic strategies in order to improve the clinical outcome for myocardial infarction patients. This review will briefly discuss recent advances in our understanding of the neutrophil functional repertoire and emerging insights of sex-specific differences in post-myocardial infarction inflammatory responses.